LFA-1 activation in NK cells and their subsets: influence of receptors, maturation, and cytokine stimulation - Urlaub, Doris; Höfer, Kristine; Müller, Martha-Lena (The journal of immunology, 2017)
The integrin LFA-1 is essential for efficient activation and for cytotoxicity of NK cells because it initiates the assembly of the immunological synapse and mediates firm adhesion to the target. LFA-1 is also needed to polarize the cytotoxic machinery of the NK cell toward the target cell. The binding affinity and avidity of integrins can be regulated via inside-out signals from other receptors. In this article, we investigate the signals necessary to activate LFA-1 in human NK cells. Our data show that LFA-1 has a low ligand-binding activity in resting human NK cells, but it can be stimulated by triggering activating receptors, such as 2B4 or CD16, or by coactivation of different receptor combinations. Short-term stimulation of freshly isolated NK cells with cytokines, such as IL-15, IL-12, or IL-18, does not activate LFA-1 but increases the responsiveness of the cells to subsequent receptor stimulation. Different NK cell subsets vary in their ability to induce LFA-1 binding activity after activating receptor stimulation. Interestingly, the NK cell subsets that are more mature and possess higher cytotoxic potential also show the highest activation of LFA-1, which correlated with the expression of the small calcium-binding protein S100A4. Our data suggest that regulation of LFA-1 is one reason for the different activity of NK cells during differentiation.